Peningkatan Kualitas Siswa dengan Pengembangan IPTEK dan Imtak di SD Al-Ma’soem Bandung - Khoiriyah, Zumrotul A’la; Aminah, Siti Nur; Auliya, Fadhilatul Fithri; Ahsani, Eva Luthfi Fakhru (Lembaga Yasin AlSys, 2022)
This study aims to improve the quality pf students in faith and piety and science and technology at SD Al Ma’soem Bandung.. The method used in this research is the field research method or direct research where the researcher goes directly to the place to be studied, with data collection using the results of interviews, observations, and documentation. Efforts can be made to improve the quality of students in the world of education, namely by developing science and technology and IMTAQ. Basically general science and religious knowledge are important foundations in creating excellent students. So the provision of religious knowledge with general knowledge is one solution and it is important to do so. With the provision of religious knowledge and general knowledge, students are able to follow the current developments but still have a good level of faith and piety. Science and technology and IMTAQ have a relationship to realize a balanced life in this world and the hereafter. The result of this study illustrate that student personality development is carried out with the IMTAQ program including the implementation of reading the Qur’an and asmaul hsuna activities, it will form an Islamic persoanality, and in the science and technology program students can use computer wisely and can make discoveries new.